2019
DOI: 10.1001/jamanetworkopen.2019.7025
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Motor Outcomes of Children With Prenatal Opioid Exposure

Abstract: Key Points Question Is prenatal opioid exposure associated with differences in childhood cognitive and motor development? Findings In this systematic review and meta-analysis of 26 studies including 1455 children exposed to prenatal opioids compared with unexposed children, prenatal opioid exposure was associated with lower cognitive scores. The largest difference was seen between ages 6 months and 6 years. Meaning The negative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
148
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(165 citation statements)
references
References 85 publications
14
148
0
3
Order By: Relevance
“…show that PME disrupts physical, behavioral, and neuronal development which persists beyond the immediate neonatal period which supports clinical studies that suggest babies born with opioid exposure are at higher risk for adverse developmental outcomes [9][10][11] .…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…show that PME disrupts physical, behavioral, and neuronal development which persists beyond the immediate neonatal period which supports clinical studies that suggest babies born with opioid exposure are at higher risk for adverse developmental outcomes [9][10][11] .…”
Section: Discussionsupporting
confidence: 73%
“…socioeconomic factors and prenatal alcohol/tobacco), indicating opioid exposure in utero may specifically disrupt motor cortex development and potentially impact motor behavior 7 . Prior studies revealed poorer motor performance in children exposed to opioids prenatally suggesting that prenatal opioid exposure produces longlasting changes in both motor behavior and in brain regions associated with motor functioning 9,10 . However, clinical studies are often complicated by significant environmental variations which are difficult to control such as the extent of prenatal care or additional prenatal substance exposures which also impact neurodevelopmental outcomes of children 11 .…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Two previous meta-analyses specific to cognitive outcomes among young children after opioid exposure have been published. 6,12 Both identified a significant negative association (ie, lower cognitive development test scores) among children with opioid exposure. Furthermore, both metaanalyses identified that the included articles were of overall poor quality and suggested that differential social, environmental, and familial risks between children with and without exposure may contribute to the observed cognitive differences.…”
Section: Introductionmentioning
confidence: 99%
“…Extended prenatal exposure to an opioid, with cessation at birth, may result in neonatal opioid withdrawal syndrome (NOWS) (1). NOWS babies are often born premature and underweight, are typically extremely irritable with inconsolable high-pitched crying, with uncontrolled and jittery limb movements, disrupted sleep, and other complications.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are significant laterlife effects, including motor and cognitive delay, with untold long-term costs (4,5). Opioids continue to be the best relief for chronic or severe pain, and as many as 28% of pregnant women are reported to have filled an opioid prescription for pain or opioid use disorder management (1). Buprenorphine, a favored agonist for maintenance therapy, results in less severe neonatal withdrawal than methadone (MTD), but both agonists have a similar rate of NOWS after birth (~50%), and both require significant ICU stay times (50).…”
Section: Introductionmentioning
confidence: 99%